Improving the Security of Video Embedding Using the CFP-SPE Method - Karthick Panneerselvam; K. Rajalakshmi; V. L. Helen Josephine; Dhivya Rajan; L. Visalatchi; K. Mahesh; Meroda Tesfaye (Journal of Engineering)
With the amount of data being transferred on a daily basis, it is becoming increasingly dangerous to save data on the Internet in the face of intruders or hackers. This study paper is one of the most effective ways to transmit information in a secure and confidential manner. The authors previously disclosed a way for embedding a secret video inside a cover video in their prior work. The writers have implemented a number of techniques to incorporate the secret video. The current work improves on the existing approach by including encryption and decryption concepts into the video embedding process. The secret data for either a large or little amount of information is put on the cover video utilising the embedding technique. Our proposed method combines compression, encryption, decryption, and secret information embedding to provide a more secure data transfer.